Geographic distribution of restriction types of Mycobacterium bovis isolates from brush-tailed possums (Trichosurus vulpecula) in New Zealand. - Collins, D. M. (Cambridge University Press, 1986)
DNA restriction endonuclease analysis was used for intra-specific typing of Mycobacterium bovis isolates from 83 brush-tailed possums (Trichosurus vulpecula) obtained between 1982 and 1984 from the three major regions in New Zealand with endemic bovine tuberculosis. All the isolates were found to be genetically very similar. Differentiation of the isolates into 33 restriction types was achieved by using high-resolution electrophoresis and the combined results from separate digestions with the restriction enzymes Bst EII, Pvu II and Bcl I. The typing system was entirely reproducible. Isolates of the same type were usually found in adjacent localities and were always limited to one of the three major regions. In some cases, isolates of the same type were found in both 1982 and 1984. The phenotypic significance of the small genetic differences identified between different isolates is unknown. The typing system will be useful for monitoring the transmission of M. bovis to other species and the future spread of different M. bovis types through possum populations.